Knowledge and Awareness of Adults towards Nocturnal Enuresis in Children among the Medina Population - Muayad Saud Albadrani; Tariq Abdulazez Alluqmani; Osama Hamed Alsehli; Meshal Saleem Alsaedi; Hassan Saleh Alrehaili; Ahmed Abdullah Aljabri; Muhammad Abubaker Tobaiqi (MDPI AG, 2024)
Background: Nocturnal Enuresis (NE) is a common problem among children that is stressful for both the child and adults. There is a lack of adults' knowledge and awareness of the NE condition. Objective: This study aimed to evaluate the adults' knowledge and awareness of NE in Medina City, Saudi Arabia. Method: A cross-sectional observational study was conducted among adults in Medina through September and October 2023, using a questionnaire composed of socio-demographic characteristics and adults' knowledge and awareness of NE. A statistical analysis was performed using SPSS software. Results: The study was conducted among 553 adults in Medina, with a mean (standard deviation [SD]) age of 37.69 (10.775). Most participants (94.8%) were Saudi nationals, of which 84.4% were females, 76.3% were married, and 97.1% were urban residents with university degrees (80.3%). The mean (SD) total score of knowledge and awareness was 4.69 (1.783) out of 9 and 6.49 (2.167) out of 12, respectively. Being female (p < 0.001), with a university degree (p = 0.002), and knowing about enuresis in children (p = 0.011) are significant factors affecting adults' knowledge with higher scores than others. Conclusions: An inadequate knowledge and awareness level of NE in children was revealed among adults living in Medina City, Saudi Arabia. These results emphasize the need for targeted educational campaigns to enhance adults' knowledge and awareness of enuresis.